Losartan improves alveolar bone dynamics in normotensive rats but not in hypertensive rats - Mulinari-santos, Gabriel [UNESP] (2019)
Hypertension is one of the main causes of premature death in the world; also, it is associated with several bone alterations. Preclinical studies have demonstrated delayed alveolar bone healing in hypertensive rats. However, losartan has been favorable for consolidation of bone grafts and reduction in active periodontitis. Therefore, losartan is suggested to be effective in bone formation stages, as well as in the synthesis of matrix proteins and mineralization.